2014
DOI: 10.1371/journal.pone.0090218
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Group Housing Strategies for the Ex-Situ Conservation of Harlequin Frogs (Atelopus spp.) Using Behavioral and Physiological Indicators

Abstract: We have established ex situ assurance colonies of two endangered Panamanian harlequin frogs, Atelopus certus and Atelopus glyphus, but observed that males fought with each other when housed as a group. Housing frogs individually eliminated this problem, but created space constraints. To evaluate the potential stress effects from aggressive interactions when grouping frogs, we housed male frogs in replicated groups of one, two, and eight. We measured aggressive behavioral interactions and fecal glucocorticoid m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
(35 reference statements)
3
14
0
Order By: Relevance
“…Similar increases in corticosterone have been observed in other amphibians in response to capture and handling (Narayan et al, 2012;Ricciardella et al, 2010;Woodley and Lacy, 2010), agitation (Davis and Maerz, 2011) and novel social environment (Cikanek et al, 2014)all components of the transportation and re-housing process.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Similar increases in corticosterone have been observed in other amphibians in response to capture and handling (Narayan et al, 2012;Ricciardella et al, 2010;Woodley and Lacy, 2010), agitation (Davis and Maerz, 2011) and novel social environment (Cikanek et al, 2014)all components of the transportation and re-housing process.…”
Section: Discussionsupporting
confidence: 68%
“…In amphibians physiological and/or behavioural changes indicative of stress have been observed following capture and handling (e.g. Narayan et al, 2012;Ricciardella et al, 2010;Woodley and Lacy, 2010), exposure to water vibrations (Davis and Maerz, 2011), and in response to a novel social environment (Cikanek et al, 2014). The amphibian hypothalamic-pituitary-interrenal axis (HPI, analogous to the mammalian hypothalamic-pituitary adrenal axis; Rollins-Smith, 2001), releases corticosterone when activated and increases in corticosterone have been observed following both infection and physical stressors in amphibians (Gabor et al, 2013b;Yao et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the frogs becoming more familiar with the new environment or individual housing over the course of the study. Cikanek et al (2014) found similar results in Panamanian harlequin frogs ( Atelopus certus and Atelopus glyphus ), with frogs maintained individually exhibiting lower faecal glucocorticoid metabolite concentrations than those maintained in groups of two or eight, and those maintained in group housing exhibiting a decline in glucocorticoid metabolite concentrations over the 4 week study period.…”
Section: Discussionsupporting
confidence: 58%
“…Raw data values for faecal glucocorticoid metabolite concentrations indicated an increase at around 3–5 days post-marking (days 17–19; Fig. 1 ), which is within the expected lag time in glucocorticoid metabolite deposition in faeces for a range of species ( Wasser et al , 2000 ; Bamberg et al , 2001 ; Martínez-Mota et al , 2008 ; Santymire et al , 2012 ; Smith et al , 2012 ) including amphibians ( Cikanek et al , 2014 ). Therefore these data were used for the post-marking time point as described above.…”
Section: Methodssupporting
confidence: 51%
“…Gagliardo et al 2008). The investment required to create facilities large enough to hold viable populations of amphibians has been cited as a limiting factor even for small species (Barber and Poole 2014; Cikanek et al 2014).…”
Section: Small Size and Low Space Requirementsmentioning
confidence: 99%